DETERMINAN KINERJA BANK UMUM SYARIAH DI INDONESIA - Intan Nauvita Dwi Utami (2021)
Quantitative research in this study aims to determine the determination of the profitability of Indonesian Sharia Commercial Banks from 2015 to 2019, where capital, liquidity, and financing risk are the variables studied. The research data uses bank financial statement data with secondary data types. Data collection was carried out using documentation techniques that were sourced from the publication of Islamic Bank financial reports. There are 14 samples used in the study with saturated sampling as a sampling technique. Hypothesis testing in this study uses Panel Data Regression Analysis with Excel and Eviews programs at a significance level of 0.05. The results of the study indicate that: (1) Capital projected with the Capital Adequacy Ratio (CAR) has a positive effect onPprofitability (ROA); (2) Liquidity projected with Financing to Deposit Ratio (FDR) has no effect on Profitability (ROA); (3) Financing risk projected with a Non Performing Ratio (FDR) has a negative effect on profitability (ROA).